A comparative study of two immunoassays of maternal placental growth factor. (3rd May 2021) - Hayes-Ryan, Deirdre; O'Donoghue, Keelin; McCarthy, Cathal; Totorika, Ainhoa; Meaney, Sarah
Abstract: Circulating maternal levels of placental growth factor correlates well with placental function and numerous studies advocate its role to help rule-out preterm pre-eclampsia. A number of automated immunoassay platforms to quantify placental growth factors are currently available. The aim of this study was to highlight the importance of developing and validating appropriate reference ranges and clinical cut-offs for immunoassays, by comparing the results obtained from two different immunoassays of placental growth factor; the Quantikine ® ELISA and the automated Triage ® test. This was a secondary subgroup analysis of samples collected as part of a prospective cross-sectional study of placental growth factors in twin pregnancy. Consenting pregnant women with a twin pregnancy, across a variety of gestations, had a single blood sample taken at a one-time point only during their pregnancy. The plasma was initially biobanked and then later analysed in batches using both immunoassays. Although the placental growth factor values of the two immunoassays correlated well ( r = 0.88, n = 178, p < .001), the actual results obtained were significantly different (mean difference 238.1 pg/ml). Poor concordance between the two immunoassays was also present, with the Triage ® test recording 36 cases as <100 pg/ml whereas the Quantikine ® ELISA identified only 4 as <100 pg/ml. Biomarker levels may vary significantly between different immunoassay platforms, highlighting the importance of developing validated clinical cut-offs for any automated immunoassay before its clinical application. These differences need to be understood to facilitate clinical utility given that placental growth factor testing is likely to be introduced into widespread clinical practice.